Frequency of Incomplete St Segment Resolution After Successful Primary Percutaneous Coronary Intervention: Incomplete ST Segment Resolution After Successful Primary Percutaneous Coronary Intervention - Jamil, Araj; Shaikh, Laraib; Ahmed, Bilal; Manzoor, Vengus; Hussain, Sabir; Hussain, Wajid; Saghir, Tahir (Pakistan Journal of Health Sciences, 2022)
The success of primary Percutaneous Coronary Intervention (PCI) can be verified on electrocardiogram through measuring ST Resolution (STR) and examination if their angiogram. Objective: The purpose of this research was to identify instances of after the primary PCI of partial STR and to investigate the characteristics associated with incomplete STR following primary PCI. Methods: At department of Interventional Cardiology of National Institute of Cardiovascular Disease (NICVD), Karachi, Pakistan, this Descriptive Cross-sectional study was conducted. The inclusion criteria set for data collection were patients with age between 18 to 65 years of both genders presented with complain of chest pain 12 hour previously and now diagnosed with acute STEMI, and undergoing successful primary PCI were included in the study. Results: Out of 196 patients, male was 74.5% while female were 25.5%. The Mean age of patients was 52.78±7.81 years. Out of 196 patients, with acute STEMI, 35.2% (69) had Incomplete STR after a successful primary PCI. When applying chi square on study variables with Incomplete STR after a successful primary PCI was found to be not associated with patient’s baseline characteristics. Conclusions: Our research discovered that a considerable proportion of patients with STEMI have Incomplete STR after first PCI. However, no correlation between STR and baseline patient characteristics was observed